DIRECTED EVOLUTION OF ENZYMES: SMALL CHANGES, BETTER BIOCATALYSTS - Teixeira, Iris S. [UNESP]; Milagre, Cintia D. F. [UNESP] (Soc Brasileira Quimica, 2020)
Biocatalysis is now a mature field, both in the laboratory and industrial scale. This approach counts on enzyme high selectivity, biodegradability, elegant control over the outcome of reaction conditions and as a possible solution to address some challenges in Green Chemistry faced by synthetic organic chemists. However, many wild-type ready-to-use enzymes were not designed to accommodate the organic substrates needed by today's demands. Or they do not fit a predefined optimum process condition or even, useful reactions are not accessible because there is no enzyme counterpart for metallo- and organocatalysts. This review will give a brief introduction on the protein engineering tools (directed evolution, rational design, and semi-rational design) and will focus on directed evolution of enzymes, their impact in chemistry with examples from production of commodity chemicals to pharmaceutical intermediates and its potential as a tool to achieve greener chemistry criteria will be discussed.
Keywords: protein engineering; biocatalysis; green chemistry; organic synthesis